Older‐Patient‐Specific Cancer Trials: A Pooled Analysis of 2, 277 Patients (A151715). (12th April 2019) - Dao, Dyda; Zemla, Tyler; Jatoi, Aminah; Freedman, Rachel A.; Hurria, Arti; Muss, Hyman; Cohen, Harvey Jay; Shulman, Lawrence N.; Citron, Marc; Budman, Daniel; McMurray, Ryan; Partridge, Ann; et al.
Abstract: Background: Less than 3% of older patients with cancer are enrolled in clinical trials. To reverse this underrepresentation, we compared older patients enrolled with older‐patient‐specific trials, defined as those designed for older patients with cancer, with those enrolled in age‐unspecified trials. Materials and Methods: We focused on individual patient data from those ≥65 years (younger patients excluded) and included all Alliance phase III adjuvant breast cancer trials from 1985–2012. Results: Among 2, 277 patients, 1, 014 had been enrolled to older‐patient‐specific and 1, 263 to age‐unspecified trials. The median age (range) in the older‐patient‐specific trials was 72 (65–89) years compared with 68 (65–84) years in the cohort of older patients in age‐unspecified trials; p < .0001. A greater percentage of patients 75 years or older had enrolled in older‐patient‐specific trials compared with the cohort of age‐unspecified trials: 26% versus 6% ( p < .0001). Median overall survival (OS) was 12.8 years (95% confidence interval [CI], 11.9–13.7) and 13.5 years (95% CI, 12.9–14.1) for older‐patient‐specific and age‐unspecified trials, respectively. OS was comparable (hazard ratio [HR], 1.08; 95% CI, 0.92–1.28; p = .34; referent: age‐unspecified trials), after adjusting for age, estrogen receptor status, tumor size, and lymph node status. Similar findings were reached for recurrence‐free survival. A lower rate of grade 3–5 adverse events (hematologic and nonhematologic) was reported in older‐patient‐specific trials (43% vs. 58%; p < .0001). Sensitivity analysis with chemotherapy only trials and subset analysis, adjusted for performance score, yielded similar OS results. Conclusion: Older‐patient‐specific trials appear to address this underrepresentation of older patients with ostensibly comparable outcomes. Clinical trial identification numbers . NCT00003088 (CALGB 9741); NCT00024102 (CALGB 49907); NCT00068601 (CALGB 40401); NCT00005970 (NCCTG N9831) Abstract : Few older cancer patients are enrolled in cancer clinical trials. This article assesses whether the development and conduct of older‐patient‐specific trials is justified, comparing outcomes of patients enrolled in trials purposely designed for older cancer patients versus age‐unspecified trials.